Performance of a novel sediment sampler as an add‐on unit for portable free‐fall penetrometers: Combining in situ geotechnical testing with sediment sampling. (8th February 2019) - Bilici, Cagdas; Stark, Nina
Abstract: The investigation of mobile and loose surficial sediment layers is essential for a comprehensive seabed characterization. Portable free‐fall penetrometers (PFFPs) can deliver in situ geomechanical information about surficial sediment layers, which are difficult to preserve with traditional sampling tools. However, PFFP data interpretation can be hampered by the lack of high‐quality physical sediment samples for further verification and calibration. In this study, four new sampler configurations are tested as add‐ons for PFFPs to conduct high‐quality sediment sampling and geotechnical profiling simultaneously. Laboratory results showed that the recovery ratio of the collected samples decreased with increasing impact velocities of the probe. For impact velocities ≥ 2 m s −1, a cylindrical sampler body performed better than a conical body reaching a higher recovery ratio with less disturbance on density and saturation. Sharper carvers also increased the recovery ratio and decreased the disturbance. Field results revealed that the sample retention was challenged by energetic hydrodynamics in combination with coarse sediments (significant wave height in excess of 2 m). Overall, utilization of suction proved to be the most promising retaining mechanism under various hydrodynamic and soil conditions. Geomechanical profiles obtained with the sampler add‐ons were successfully calibrated to records obtained with the traditional PFFP tip geometries. In conclusion, the study introduced a novel sediment sampler configuration suitable for simultaneous geotechnical seabed profiling and sediment sampling using PFFP and provided insights into the impacts of sampling mechanisms on sample quality.